Efficiency of tube settler at various angle of inclinations in controlled discharges - Bhatta, Prashant; Amatya, Iswar Man (Journal of Innovations in Engineering Education, 2020)
High-rate tube settlers are a cost-effective way to update and improve the capacity and efficiency of treatment plants, particularly sedimentation tanks. They take up far less area than traditional sedimentation tanks, in addition to being more efficient. For the Nayabazar Townplanning Groundwater Project (NTGWP), the study aims to calculate the turbidity removal efficiency of tube settlers at various angles of inclination with changing discharge . The study has been carried out at varying flows of 560 lit/min, 630 lit/min, and 690 lit/min for the 77° inclination angle and 60° inclination angle, and the data were analyzed to find the best flow conditions. The removal efficiencies of tube settlers increased for each flow condition at 60º inclination compared to 77° inclination, but decreased as the discharge increased.